New actions and land uses in the historical heritage: the case study of one of the oldest underground water tanks in Madrid (Spain) - María Jesús Rosado-García; Susana López-Querol; Daniel Crespo Delgado (Heliyon, 2022)
The preservation of architectural heritage in Europe is generally associated with the recovery of monumental buildings such as churches and castles, leaving behind a high amount of other historical constructions of civil and industrial architecture that exist in an old country like Spain. High efforts have been devoted by professionals from very different fields aiming to recover and enhance engineering works such as bridges, but the particular case of hydraulic works deserves special attention because it has remained hidden for centuries and sometimes continues to be ignored by society and many institutions. This type of architectural heritage, in the form of underground deposits that represents the case under study in this research, occupies a large area in cities such as Madrid and must be preserved to relieve the pressures of adapting them to accommodate other uses of the land that they occupy. In this paper, the complexity of material characterization and calculation of the Mayor water tank in Madrid (Spain), as an example of this type of construction, is presented. This reservoir currently supplies drinking water to a large part of the city and can accommodate a park on its surface without altering an original 150-year-old structure. As the main conclusion of this research, and in the absence of detailed studies of pathologies, tests, characterization of materials and the terrain, it is recommended to avoid loads greater than 30 kN/m2 in the existing structure, hence the current stresses are not substantially exceeded. This is a recommendation to preserve the historical heritage of this structure against economic and political perspectives that push for a substantial change in its use. This research is an example that can easily be extrapolated to other similar historical infrastructures aiming to guarantee their prevalence in the future.